Pronounced energy restriction with elevated protein intake results in no change in proteolysis and reductions in skeletal muscle protein synthesis that are mitigated by resistance exercise. Issue 1 (12th September 2017) - Hector, Amy J.; McGlory, Chris; Damas, Felipe; Mazara, Nicole; Baker, Steven K.; Phillips, Stuart M.
Abstract : Preservation of lean body mass (LBM) may be important during dietary energy restriction (ER) and requires equal rates of muscle protein synthesis (MPS) and muscle protein breakdown (MPB). Currently, the relative contribution of MPS and MPB to the loss of LBM during ER in humans is unknown. We aimed to determine the impact of dietary protein intake and resistance exercise on MPS and MPB during a controlled short‐term energy deficit. Adult men (body mass index, 28.6 ± 0.6 kg/m 2 ; age 22 ± 1 yr) underwent 10 d of 40%‐reduced energy intake while performing unilateral resistance exercise and consuming lower protein (1.2 g/kg/d, n = 12) or higher protein (2.4 g/kg/d, n = 12). Pre‐ and postintervention testing included dual‐energy X‐ray absorptiometry, primed constant infusion of ring ‐[ 13 C6 ]phenylalanine, and 15 [N]phenylalanine to measure acute postabsorptive MPS and MPB; D2 O to measure integrated MPS; and gene and protein expression. There was a decrease in acute MPS after ER (higher protein, 0.059 ± 0.006 to 0.051 ± 0.009%/h; lower protein, 0.061 ± 0.005 to 0.045 ± 0.006%/h; P < 0.05) that was attenuated with resistance exercise (higher protein, 0.067 ± 0.01%/h; lower protein, 0.061 ± 0.006%/h), and integrated MPS followed a similar pattern. There was no change in MPB (energy balance, 0.080 ± 0.01%/hr; ER rested legs, 0.078 ± 0.008%/hr; ER exercised legs, 0.079 ± 0.006%/hr). We conclude that a reduction in MPS is the main mechanism that underpins LBM loss early in ER in adult men.—Hector, A. J., McGlory, C., Damas, F., Mazara, N., Baker, S. K., Phillips, S. M. Pronounced energy restriction with elevated protein intake results in no change in proteolysis and reductions in skeletal muscle protein synthesis that are mitigated by resistance exercise. FASEB J. 32, 265‐275 (2018). www.fasebj.org